The effect of population and tourism factors on Covid‐19 cases in Italy: Visual data analysis and forecasting approach. (14th December 2021) - Uğuz, Sezer; Yağanoğlu, Mete; Özyer, Barış; Özyer, Gülşah Tümüklü; Tokdemir, Gül
Abstract: At the beginning of 2020, the new coronavirus disease (Covid‐19), a deadly viral illness, is declared as a public health emergency situation by WHO. Consequently, it is accepted as pandemic that affected millions of people worldwide. Italy is one of the most affected countries by Covid‐19 disease among the world. In this article, our main goal is to investigate the effect of intensity of Covid‐19 cases based on the population size and tourism factors in certain regions of Italy by visual data analysis. The regions of Lombardia, Veneto, Campania, Emilia‐Romagna, Piemonte are the top five regions covering 58.50% of the total Covid‐19 cases diagnosed in Italy. It has been shown by visual data analysis that population and tourism factors play an important role in the spread of Covid‐19 cases in these five regions. In addition, a prediction model was created using Bi‐LSTM and ARIMA algorithms to forecast the number of Covid‐19 cases occurring in these five regions in order to take early action. We can conclude that these northern regions have been affected mostly by Covid‐19 and the distribution of the resident population and tourist flow factors affected the number of Covid‐19 cases in Italy.